A descriptive study of various cranio-facial features as sex determinants - Castor, Jean Michelle C.; Magtanong, Danilo L. (Adviser).
The study of the skull is a keystone in the Dental discipline, taking this into consideration, the researcher chose to pursue a study on skulls. This paper describes the various Cranio-facial features as sex determinants for the sample skulls. The study aimed to determine if Cranio-facial features can accurately identify the sex of the sample skulls. The thirty sample skulls were taken from the Department of Anatomy of the College of Medicine and the Department of Orthodontics of the College of Dentistry of the University of the Philippines. The skulls were then brought to the National Bureau of Investigations (NBI). A pre-coded table ( Appendix C ) was constructed with the aid of Dr. Eduardo Antonio C. Kalalo of the Department of Dentistry of the NBI, the pre-coded table was used to tabulate the data of the study. Using the various Cranio-facial features as determinants, the sex of the skulls were then identified and verified. The findings revealed that each Cranio-facial feature can be accurate determinants of sex from seventy-seven ( 77%) - one hundred percent (100%).
Seminar Paper--Doctor of Dental Medicine--University of the Philippines Manila.